2021
DOI: 10.1038/s41535-021-00326-5
|View full text |Cite
|
Sign up to set email alerts
|

Orbital structure of the effective pairing interaction in the high-temperature superconducting cuprates

Abstract: The nature of the effective interaction responsible for pairing in the high-temperature superconducting cuprates remains unsettled. This question has been studied extensively using the simplified single-band Hubbard model, which does not explicitly consider the orbital degrees of freedom of the relevant CuO2 planes. Here, we use a dynamical cluster quantum Monte Carlo approximation to study the orbital structure of the pairing interaction in the three-band Hubbard model, which treats the orbital degrees of fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…1F and 2F shows that the charge stripe appears at higher energy scale instead. Previous DCA studies have observed a finite-temperature transition to the d-wave superconducting state (21,38). Now that DCA also finds evidence for fluctuating stripes, both in the spin and charge sector, it is natural to ask how they affect the formation of Cooper pairs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1F and 2F shows that the charge stripe appears at higher energy scale instead. Previous DCA studies have observed a finite-temperature transition to the d-wave superconducting state (21,38). Now that DCA also finds evidence for fluctuating stripes, both in the spin and charge sector, it is natural to ask how they affect the formation of Cooper pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The pairing tendencies are accessed by measuring the static pairing correlation function in the d -wave channel , where destroys a singlet pair of electrons with d -wave symmetry. We also determined the structure of the pairing interaction by explicitly solving the Bethe–Salpeter equation in the particle–particle singlet channel to obtain its leading eigenvalues and eigenvectors ( 22 , 38 ). Due to the large cluster sizes and the self-consistency loop, our DCA calculations are significantly more expensive than the corresponding DQMC calculations.…”
Section: Modelmentioning
confidence: 99%
“…Some zero temperature techniques, such as the tensor network 30,31 and the path-constrained auxiliary-field quantum Monte Carlo 32 can access large lattices, but have difficulty in calculating the single-and two-particle dynamical response functions probed by angle-resolve photoemission (ARPES), inelastic neutron scattering (INS), and resonant inelastic x-ray scattering (RIXS) experiments. Importantly, contrasting results obtained from the singleband model with arXiv:2106.04017v1 [cond-mat.str-el] 8 Jun 2021 multi-orbital models adds another layer of difficulty, since the inclusion of the O 2p orbitals significantly increases the complexity of the problem 29,[33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…in the one-band Hubbard model) where the insulating (or Mott) gap appears between the lower and upper Hubbard bands. On doping the charge-transfer insulator, the holes primarily go into the oxygen orbitals and another band appears at the Fermi level referred to as the Zhang-Rice singlet band (ZRSB) [58,71,72]. Zhang-Rice singlets are characterized by singlet-states formed between the Cu orbital and the adjacent O orbitals [73,74].…”
Section: Model and Methodsmentioning
confidence: 99%
“…It is thus important to investigate more realistic models, such as the three-band Emery-VSA model that accounts for copper-oxygen hybridization of the single band that crosses the Fermi surface [50,51]. A variety of theoretical methods [13,36,[52][53][54][55][56][57][58] revealed many similarities with the one-band Hubbard model, but also differences related to the role of oxygen [59][60][61].…”
Section: Introductionmentioning
confidence: 99%